Revisiting the malaria hypothesis: accounting for polygenicity and pleiotropy. Issue 4 (April 2022) - Ebel, Emily R.; Uricchio, Lawrence H.; Petrov, Dmitri A.; Egan, Elizabeth S.
Abstract : The malaria hypothesis predicts local, balancing selection of deleterious alleles that confer strong protection from malaria. Three protective variants, recently discovered in red cell genes, are indeed more common in African than European populations. Still, up to 89% of the heritability of severe malaria is attributed to many genome-wide loci with individually small effects. Recent analyses of hundreds of genome-wide association studies (GWAS) in humans suggest that most functional, polygenic variation is pleiotropic for multiple traits. Interestingly, GWAS alleles and red cell traits associated with small reductions in malaria risk are not enriched in African populations. We propose that other selective and neutral forces, in addition to malaria prevalence, explain the global distribution of most genetic variation impacting malaria risk. Highlights: In malaria-endemic populations, the malaria hypothesis predicts balancing selection on protective loci that interfere with red blood cell (RBC) function. Novel variants in the RBC genes PIEZO1, ATP2B4, and GYPA/GYPB are associated with strong protection from severe malaria and are more common in Africans than Europeans, consistent with the malaria hypothesis. Genome-wide association studies (GWAS) attribute most of the heritability of severe malaria risk to many loci with small effects spread across the genome. African populations are not enriched for small-effect alleles associated with protection from severe malaria. Similarly, healthy RBC traits associated with reduced Plasmodium falciparum growth in vitro are not positively associated with African ancestry. Pervasive pleiotropy may limit adaptation in complex traits. Therefore, host variation that impacts malaria may not necessarily conform to the malaria hypothesis.